Preparation method of carbon dot-based super-strong hydrogel

By using specific carbon dots as nanofillers and salting-out assisted progressive stretching method, combined with the Hofmeister effect of polyvinyl alcohol, a carbon dot-based super hydrogel was constructed, which solved the mechanical properties of traditional hydrogels. The contradiction achieves high strength and toughness while having good frost resistance.

CN119350654AActive Publication Date: 2025-01-24SOUTHWEST FORESTRY UNIVERSITY

Patent Information

Application Number
CN202411363913.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-28
Publication Date
2025-01-24
Estimated Expiration
2044-09-28

AI Technical Summary

Technical Problem

There is a contradiction between strength and toughness in terms of mechanical properties of existing hydrogel materials, and it is difficult to achieve high strength and high toughness at the same time. The compatibility and interface interaction of nanofillers are limited, which affects the mechanical properties.

Method used

Specific carbon dots (citric acid carbon dots, tannic acid carbon dots, malic acid carbon dots or bark carbon dots) are used as nanofillers, and the salting-out assisted progressive stretching method is combined with the Hofmeister effect of polyvinyl alcohol. to construct super-strong hydrogels.

Benefits of technology

The ultra -high stretching strength and toughness of hydrogel can reach 156MPa and 225.2mj/m3, and the material introduces salt solutions in the tight structure, which has good freezing resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119350654A_ABST
    Figure CN119350654A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of hydrogel materials, and particularly relates to a preparation method of carbon dot-based super-strong hydrogel. The carbon-dot-based super-strong hydrogel is prepared by taking specific carbon dots (citric acid carbon dots, tannic acid carbon dots, malic acid carbon dots or bark carbon dots) as nano-filler and salting-out-assisted progressive stretching, the specific carbon dots are used as the nano-filler, and the HofMichast effect sensitive characteristic of polyvinyl alcohol is utilized, so that the carbon-dot-based super-strong hydrogel is prepared. Carbon dots and salting-out progressive stretching are combined to construct the super-strong hydrogel, and the super-strong hydrogel is simple in preparation process and excellent in performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of hydrogel materials, and in particular to a method for preparing a carbon-dot-based super-strong hydrogel. Background Art

[0002] Hydrogels are widely used in wearable electronics, soft robots, nano-friction generators, biomedicine, and solid electrolytes due to their unique conductivity, flexibility, and three-dimensional network structure. However, traditional hydrogels are composed of a single hydrophilic polymer network, lack energy dissipation mechanisms, and are susceptible to stress concentration. Most of them show the disadvantages of weak mechanical properties and toughness. In addition, there is an inherent contradiction between the strength and toughness of hydrogels. Improving the mechanical strength often leads to hardening of the material, making it difficult for the hydrogel to have both high toughness and high strength. This poor mechanical property greatly limits the application of such hydrogels. Recently, high-strength hydrogels have been developed through strategies such as constructing double networks, organic-inorganic hybridization, densification, multiple interactions and directional freezing. The hydrogels constructed by these methods show better mechanical strength, but despite this, it is still difficult for the material to reach a fracture strength of 50MPa and a thermal conductivity of 200MJ m -3 Therefore, it is necessary to design and develop high-strength and high-toughness hydrogels.

[0003] Nanofillers (carbon nanotubes, graphene, and MXene, etc.) have attracted great attention due to their interfacial effects with polymers. However, nanofillers generally have poor compatibility with the matrix, resulting in poor dispersibility, which undermines the effectiveness of this reinforcement strategy. Moreover, this interfacial interaction is usually based on weak physical effects and limited chemical bonding, which has limited improvement in the mechanical properties of hydrogels. In addition, nanofillers are expensive and cumbersome to prepare. Subsequently, carbon dots gradually came into people's field of vision. As a new member of the "carbon family", carbon dots (CDs) are carbon nanoparticles with a size of less than 10 nm. They were accidentally discovered in 2004 when preparing single-walled carbon nanotubes for electrophoresis purification, and luminescent carbon was prepared by surface passivation in 2006. Since then, this field has attracted many researchers due to its excellent optical properties, conductivity, low toxicity, and high biocompatibility. However, carbon dots are rarely used to improve the mechanical properties of composite materials. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing a carbon dot-based super strong hydrogel to solve the problems existing in the above-mentioned prior art and realize the preparation of the super strong hydrogel.

[0005] To achieve the above object, the present invention provides the following solutions:

[0006] One of the technical solutions of the present invention is to provide a method for preparing a carbon dot-based super hydrogel, the steps comprising:

[0007] Using a carbon source as a raw material and water as a solvent, a carbon dot solution is prepared through firing and cooling;

[0008] The carbon dot solution and polyvinyl alcohol are used as reactants, and subjected to high temperature reaction and freeze-thaw cycles to obtain a carbon dot-polyvinyl alcohol hydrogel;

[0009] The carbon dot-polyvinyl alcohol hydrogel is subjected to salting-out assisted progressive stretching and then immersed in a sodium citrate solution to obtain the carbon dot-based super strong hydrogel;

[0010] The carbon source is at least one of citric acid, tannic acid, malic acid and bark.

[0011] Furthermore, the usage ratio of the carbon source to water is 10g:100mL.

[0012] Furthermore, the firing temperature is 160° C. and the firing time is 8 hours.

[0013] Furthermore, the mass ratio of the carbon dot solution to polyvinyl alcohol is 17:3.

[0014] Furthermore, the temperature of the high temperature reaction is 90° C. and the time is 3 hours.

[0015] Furthermore, the freeze-thaw cycle is freezing at -20°C for 8 hours, then thawing at 20°C for 3 hours, and the freeze-thaw cycle is repeated at least once.

[0016] Furthermore, the step of salting out assisted progressive stretching is:

[0017] The carbon dot-polyvinyl alcohol hydrogel was immersed in a sodium citrate solution for 12 hours and then subjected to gradual stretching.

[0018] Preferably, the concentration of the sodium citrate solution is 2 mol / L.

[0019] Preferably, the deformation amount of the progressive stretching is 300%.

[0020] During the salting-out-assisted progressive stretching process, the hydrogel becomes more compact, achieving the purpose of enhancing mechanical properties.

[0021] Furthermore, the immersion time in the sodium citrate solution is 12 hours, and the concentration of the sodium citrate solution is 2 mol / L.

[0022] In order to improve the mechanical properties of hydrogels, the present invention designs a method in which specific carbon dots (citric acid carbon dots, tannic acid carbon dots, malic acid carbon dots or bark carbon dots) act as nanofillers and salting-out assisted progressive stretching. 2The crystal nucleus can give the material good interfacial interactions (such as ππ stacking, CH-π, etc.). Moreover, after carbonization, the functional groups of the carbonized precursor can be well retained and have good dispersibility. In addition, the mechanical properties of the hydrogel are enhanced through non-covalent bonds between specific carbon points, polyethylene and sodium ions, including π-π, CH-π, van der Waals force and ionic bonds.

[0023] The second technical solution of the present invention is to provide a carbon dot-based super strong hydrogel prepared by the above preparation method.

[0024] The present invention discloses the following technical effects:

[0025] The specific carbon dot-based super-strong hydrogel of the present invention is prepared by using citric acid carbon dots, tannic acid carbon dots, malic acid carbon dots or bark carbon dots as nanofillers and salting-out assisted progressive stretching, and utilizing the Hofmeister effect sensitive characteristics of polyvinyl alcohol (PVA) to combine carbon dots and progressive stretching to construct a hydrogel with super-strong mechanical properties.

[0026] The specific carbon dots used in the present invention (citric acid carbon dots, tannic acid carbon dots, malic acid carbon dots or bark carbon dots) not only have attractive sp 2 The crystal nucleus can give the material good interface interactions (such as π-π stacking, CH-π, etc.), and the carbonized citric acid, tannic acid, malic acid and bark can well retain the functional groups of the carbonized precursors, have good dispersibility and introduce a large number of physical cross-linking reaction sites for the polyvinyl alcohol hydrogel, which gives the hydrogel ultra-high tensile strength and toughness. Moreover, the salt solution introduced in the process of compact structure gives the hydrogel good antifreeze ability. The preparation process of the hydrogel is simple and the performance is excellent. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0028] Figure 1 The stress-strain curves of the hydrogels prepared in Example 1 and Comparative Examples 6-7;

[0029] Figure 2 The stress-strain curves of the hydrogels prepared from different carbon sources in Examples 1 to 4;

[0030] Figure 3 This is the stress-strain curve of the hydrogel prepared in Comparative Example 1;

[0031] Figure 4 This is the stress-strain curve of the hydrogel prepared in Comparative Example 2;

[0032] Figure 5 This is the stress-strain curve of the hydrogel prepared in Comparative Example 3;

[0033] Figure 6 This is the stress-strain curve of the hydrogel prepared in Comparative Example 4;

[0034] Figure 7 This is the stress-strain curve of the hydrogel prepared in Comparative Example 5;

[0035] Figure 8 The DSC graphs of the hydrogels prepared in Example 1 and Comparative Examples 1 to 5;

[0036] Fig. 9 This is a schematic diagram of the process flow of Example 1. DETAILED DESCRIPTION

[0037] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0038] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0039] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0040] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0041] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0042] Unless otherwise specified, the room temperature in the specific embodiments of the present invention refers to 25±5°C.

[0043] The raw materials and reagents used in the specific embodiments of the present invention are all commercially available products.

[0044] Example 1

[0045] The preparation steps of citric acid carbon dot-based super hydrogel are as follows:

[0046] S1. Add 10 g of citric acid to 100 mL of deionized water, place in a pressure-resistant reaction bottle, heat to 160° C. and react for 8 h. The reaction vessel is naturally cooled to room temperature to obtain a citric acid carbon dot solution.

[0047] S2, citric acid carbon dot solution (34 g) and polyvinyl alcohol (6 g) were mixed and reacted at 90° C. for 3 h. After the mixed solution was cooled to room temperature, the obtained reaction product was subjected to freeze-thaw cycle treatment (freeze-thaw cycle was freezing at -20° C. for 8 h, then thawing at 20° C. for 3 h, and freezing-thawing was repeated 2 times, for a total of 3 freezing-thawing times) to obtain citric acid carbon dot-polyvinyl alcohol hydrogel;

[0048] S3. The citric acid carbon dot-polyvinyl alcohol hydrogel obtained in step S2 was immersed in a 2 mol / L sodium citrate solution for 12 h, then progressively stretched to a deformation of 300%, and immersed in a 2 mol / L sodium citrate solution for 12 h again to obtain a citric acid carbon dot-based super hydrogel, recorded as PVA-CDYSY.

[0049] Fig. 9 This is a schematic diagram of the process flow of Example 1.

[0050] Example 2

[0051] The preparation steps of eucalyptus bark carbon dot-based super hydrogel are as follows:

[0052] S1. Add 10 g of eucalyptus bark into 100 mL of deionized water, place the mixture in a pressure-resistant reaction bottle, heat it to 160° C. and react for 8 h. The reaction vessel is naturally cooled to room temperature to obtain a eucalyptus bark carbon dot solution.

[0053] S2, eucalyptus bark carbon dot solution (34 g) and polyvinyl alcohol (6 g) were mixed and reacted at 90° C. for 3 h. After the mixed solution was cooled to room temperature, the obtained reaction product was subjected to freeze-thaw cycle treatment (freeze-thaw cycle was freezing at -20° C. for 8 h, then thawing at 20° C. for 3 h, and freezing-thawing was repeated 2 times, for a total of 3 freezing-thawing times) to obtain eucalyptus bark carbon dot-polyvinyl alcohol hydrogel;

[0054] S3. The eucalyptus bark carbon dot-polyvinyl alcohol hydrogel obtained in step S2 is immersed in a 2 mol / L sodium citrate solution for 12 hours, then progressively stretched to a deformation of 300%, and immersed in a 2 mol / L sodium citrate solution again for 12 hours to obtain a eucalyptus bark carbon dot-based super strong hydrogel.

[0055] Example 3

[0056] The preparation steps of tannic acid carbon dot-based super hydrogel are as follows:

[0057] S1. Add 10 g of tannic acid to 100 mL of deionized water, place in a pressure-resistant reaction bottle, heat to 160° C. and react for 8 h. The reaction vessel is naturally cooled to room temperature to obtain a tannic acid carbon dot solution.

[0058] S2, tannic acid carbon dot solution (34 g) and polyvinyl alcohol (6 g) were mixed and reacted at 90° C. for 3 h. After the mixed solution was cooled to room temperature, the obtained reaction product was subjected to freeze-thaw cycle treatment (freeze-thaw cycle was freezing at -20° C. for 8 h, then thawing at 20° C. for 3 h, and freezing-thawing was repeated 2 times, for a total of 3 freezing-thawing times) to obtain tannic acid carbon dot-polyvinyl alcohol hydrogel;

[0059] S3. The tannic acid carbon dot-polyvinyl alcohol hydrogel obtained in step S2 is immersed in a 2 mol / L sodium citrate solution for 12 h, then progressively stretched to 300% deformation, and immersed in a 2 mol / L sodium citrate solution for 12 h again to obtain a tannic acid carbon dot-based super strong hydrogel.

[0060] Example 4

[0061] The preparation steps of malic acid carbon dot-based super hydrogel are as follows:

[0062] S1. Add 10 g of malic acid into 100 mL of deionized water, place in a pressure-resistant reaction bottle, heat to 160° C. and react for 8 h. The reaction vessel is naturally cooled to room temperature to obtain a malic acid carbon dot solution.

[0063] S2, malic acid carbon dot solution (34 g) and polyvinyl alcohol (6 g) were mixed and reacted at 90° C. for 3 h. After the mixed solution was cooled to room temperature, the obtained reaction product was subjected to freeze-thaw cycle treatment (freeze-thaw cycle was freezing at -20° C. for 8 h, then thawing at 20° C. for 3 h, and freezing-thawing was repeated 2 times, for a total of 3 freezing-thawing times) to obtain malic acid carbon dot-polyvinyl alcohol hydrogel;

[0064] S3. The malic acid carbon dot-polyvinyl alcohol hydrogel obtained in step S2 is immersed in a 2 mol / L sodium citrate solution for 12 h, then progressively stretched to 300% deformation, and immersed in a 2 mol / L sodium citrate solution for 12 h again to obtain a malic acid carbon dot-based super strong hydrogel.

[0065] Comparative Example 1

[0066] The preparation steps of polyvinyl alcohol hydrogel are as follows:

[0067] Polyvinyl alcohol (6 g) was mixed with deionized water (34 g), reacted at 90°C for 3 h, and after the reaction product was cooled to room temperature, freeze-thaw cycle treatment was performed (freeze-thaw cycle was freezing at -20°C for 8 h, then thawing at 20°C for 3 h, freeze-thaw was repeated 2 times, a total of 3 freeze-thaw cycles) to obtain polyvinyl alcohol hydrogel, recorded as PVA.

[0068] Comparative Example 2

[0069] The preparation steps of citric acid-polyvinyl alcohol hydrogel are as follows:

[0070] Polyvinyl alcohol (6 g), citric acid (4 g) and deionized water (30 g) were mixed and reacted at 90°C for 3 h. After the reaction product was cooled to room temperature, it was subjected to freeze-thaw cycle treatment (the freeze-thaw cycle was freezing at -20°C for 8 h, then thawing at 20°C for 3 h, and the freeze-thaw cycle was repeated 2 times, for a total of 3 freeze-thaw cycles) to obtain citric acid-polyvinyl alcohol hydrogel, recorded as PVA-CA.

[0071] Comparative Example 3

[0072] The preparation steps of citric acid carbon dots-polyvinyl alcohol hydrogel are as follows:

[0073] S1. Add 10 g of citric acid to 100 mL of deionized water, place in a pressure-resistant reaction bottle, heat to 160° C. and react for 8 h. The reaction vessel is naturally cooled to room temperature to obtain a citric acid carbon dot solution.

[0074] S2, citric acid carbon dot solution (34g) and polyvinyl alcohol (6g) were mixed and reacted at 90°C for 3h. After the mixed solution was cooled to room temperature, the reaction product was subjected to freeze-thaw cycle treatment (freeze-thaw cycle was freezing at -20°C for 8h, then thawing at 20°C for 3h, freezing-thawing was repeated 2 times, for a total of 3 freeze-thaw cycles) to obtain citric acid carbon dot-polyvinyl alcohol hydrogel, recorded as PVA-CD.

[0075] Comparative Example 4

[0076] The preparation steps of citric acid carbon dots-polyvinyl alcohol hydrogel after salting out treatment are as follows:

[0077] S1. Add 15 g of citric acid to 100 mL of deionized water, place in a pressure-resistant reaction bottle, heat to 160° C. and react for 8 h. The reaction vessel is naturally cooled to room temperature to obtain a citric acid carbon dot solution.

[0078] S2, citric acid carbon dot solution (34 g) and polyvinyl alcohol (6 g) were mixed and reacted at 90° C. for 3 h. After the mixed solution was cooled to room temperature, the obtained reaction product was subjected to freeze-thaw cycle treatment (freeze-thaw cycle was freezing at -20° C. for 8 h, then thawing at 20° C. for 3 h, and freezing-thawing was repeated 2 times, for a total of 3 freezing-thawing times) to obtain citric acid carbon dot-polyvinyl alcohol hydrogel;

[0079] S3. Soak the citric acid carbon dots-polyvinyl alcohol hydrogel obtained in step S2 in a 2 mol / L sodium citrate solution for 12 h to obtain the citric acid carbon dots-polyvinyl alcohol hydrogel after salting out treatment, which is recorded as PVA-CDY.

[0080] Comparative Example 5

[0081] The preparation steps of citric acid carbon dots-polyvinyl alcohol hydrogel after salting-out assisted progressive stretching are as follows:

[0082] S1. Add 10 g of citric acid to 100 mL of deionized water, place in a pressure-resistant reaction bottle, heat to 160° C. and react for 8 h. The reaction vessel is naturally cooled to room temperature to obtain a citric acid carbon dot solution.

[0083] S2, citric acid carbon dot solution (34 g) and polyvinyl alcohol (6 g) were mixed and reacted at 90° C. for 3 h. After the mixed solution was cooled to room temperature, the obtained reaction product was subjected to freeze-thaw cycle treatment (freeze-thaw cycle was freezing at -20° C. for 8 h, then thawing at 20° C. for 3 h, and freezing-thawing was repeated 2 times, for a total of 3 freezing-thawing times) to obtain citric acid carbon dot-polyvinyl alcohol hydrogel;

[0084] S3. Soak the citric acid carbon dot-polyvinyl alcohol hydrogel obtained in step S2 in a 2 mol / L sodium citrate solution for 12 h, and then gradually stretch it to 300% deformation to obtain the citric acid carbon dot-polyvinyl alcohol hydrogel after salting-out assisted gradual stretching, which is recorded as PVA-CDYS.

[0085] Comparative Example 6

[0086] The preparation steps of citric acid carbon dot-based super hydrogel fired at 140°C are as follows:

[0087] S1. Add 10 g of citric acid to 100 mL of deionized water, place in a pressure-resistant reaction bottle, heat to 140° C. and react for 8 h. The reaction vessel is naturally cooled to room temperature to obtain a citric acid carbon dot solution.

[0088] S2, citric acid carbon dot solution (34 g) and polyvinyl alcohol (6 g) were mixed and reacted at 90° C. for 3 h. After the mixed solution was cooled to room temperature, the obtained reaction product was subjected to freeze-thaw cycle treatment (freeze-thaw cycle was freezing at -20° C. for 8 h, then thawing at 20° C. for 3 h, and freezing-thawing was repeated 2 times, for a total of 3 freezing-thawing times) to obtain citric acid carbon dot-polyvinyl alcohol hydrogel;

[0089] S3. The citric acid carbon dot-polyvinyl alcohol hydrogel obtained in step S2 is immersed in a 2 mol / L sodium citrate solution for 12 h, then progressively stretched to 300% deformation, and immersed in a 2 mol / L sodium citrate solution again for 12 h to obtain a citric acid carbon dot-based super strong hydrogel.

[0090] Comparative Example 7

[0091] The preparation steps of citric acid carbon dot-based super hydrogel fired at 180°C are as follows:

[0092] S1. Add 10 g of citric acid to 100 mL of deionized water, place in a pressure-resistant reaction bottle, heat to 180° C. and react for 8 h. The reaction vessel is naturally cooled to room temperature to obtain a citric acid carbon dot solution.

[0093] S2, citric acid carbon dot solution (34 g) and polyvinyl alcohol (6 g) were mixed and reacted at 90° C. for 3 h. After the mixed solution was cooled to room temperature, the obtained reaction product was subjected to freeze-thaw cycle treatment (freeze-thaw cycle was freezing at -20° C. for 8 h, then thawing at 20° C. for 3 h, and freezing-thawing was repeated 2 times, for a total of 3 freezing-thawing times) to obtain citric acid carbon dot-polyvinyl alcohol hydrogel;

[0094] S3. The citric acid carbon dot-polyvinyl alcohol hydrogel obtained in step S2 is immersed in a 2 mol / L sodium citrate solution for 12 h, then progressively stretched to 300% deformation, and immersed in a 2 mol / L sodium citrate solution again for 12 h to obtain a citric acid carbon dot-based super strong hydrogel.

[0095] Test example

[0096] The hydrogels prepared in Examples 1 to 4 and Comparative Examples 1 to 7 were subjected to mechanical property testing and toughness calculation according to the following methods. The results are shown in Table 1.

[0097] The hydrogels prepared in Examples 1 to 4 and Comparative Examples 1 to 7 were cut into rectangular specimens (4 cm×2 mm×1 mm) and subjected to tensile property tests at room temperature. Uniaxial tensile measurements were performed using an electronic universal testing machine (Shenzhen Sun Technology Co., Ltd., China) at an extension speed of 80 mm / min.

[0098] Toughness is calculated based on the area under the stress-strain curve using the following formula:

[0099] △U=σdε

[0100] Where σ and ε are the stress and strain of the hydrogel, respectively.

[0101] Table 1

[0102]

[0103]

[0104] It can be seen from the data in Table 1 that the tensile strength and toughness of the hydrogel prepared in Example 1 are the largest, reaching 156 MPa and 225.2 MJ / m 3 . And from the data changes of comparative examples 1 to 5, it can be seen that the mechanical properties of the hydrogel are gradually enhanced, indicating that the present invention uses citric acid carbon dots as nanofillers of polyvinyl alcohol hydrogel, salting-out assisted progressive stretching, and soaking after progressive stretching have a certain effect on the mechanical properties of the hydrogel. Similarly, carbon dots have universality. The hydrogels prepared by carbon dots fired with eucalyptus bark, malic acid and tannic acid all have super strong mechanical properties. At the same time, citric acid carbon dots fired at different temperatures also have good mechanical properties.

[0105] Figure 1 The stress-strain curves of the hydrogels prepared in Example 1 and Comparative Examples 6-7 are shown in FIG. Figure 1 It can be seen that the mechanical properties of the hydrogels prepared based on citric acid carbon dots fired at 140℃, 160℃ and 180℃ increased from 110.61MPa to 156MPa and then decreased to 125.03MPa, but the deformation showed a trend of positive correlation with temperature. This is because the structure and surface properties of carbon dots may change with the increase of firing temperature. The carbon dots fired at 140℃ have a lower degree of graphitization and a higher number of functional groups, which leads to a weaker interaction with polyvinyl alcohol hydrogel, thereby reducing the mechanical properties. The carbon dots fired at 160℃ have a higher degree of graphitization and more optimized surface properties, which makes them more firmly bonded to the hydrogel, thereby improving the mechanical properties. Further increase in temperature to 180℃ leads to excessive graphitization or excessive structural changes of carbon dots, which reduces their interaction in the hydrogel, resulting in a slight decrease in mechanical properties, but a significant increase in deformation. This may be because high-temperature carbon dots have a greater influence on the network structure of the hydrogel, resulting in improved flexibility of the material.

[0106] Figure 2 The stress-strain curves of the hydrogels prepared from different carbon sources in Examples 1 to 4 are shown in FIG. Figure 2It can be seen that the tensile strength and toughness of the hydrogels prepared based on citric acid carbon dots, eucalyptus bark carbon dots, tannic acid carbon dots and malic acid carbon dots are 150 MPa, 85.85 MPa, 52.23 MPa, 129.37 MPa and 225.2 MJ / m 3 、148.6MJ / m 3 、86.5MJ / m 3 、202.8MJ / m 3 This is because the preparation of citric acid carbon dots involves the chemical reaction of citric acid to generate carbon dots, which usually have good dispersibility and surface functionalization, and can form strong crosslinks with polyvinyl alcohol, thereby improving the tensile strength and toughness of the hydrogel. Eucalyptus bark carbon dots are derived from plant extracts and contain complex natural organic components. The influence of these components leads to poor dispersibility and interfacial binding ability in hydrogels, resulting in relatively low tensile strength. Tannic acid carbon dots have a complex structure and contain multiple phenolic hydroxyl groups, which leads to poor crosslinking in hydrogels, thereby affecting mechanical properties and toughness. Malic acid carbon dots have moderate dispersibility and interaction with polyvinyl alcohol, which leads to the tensile strength and toughness of their hydrogels being in the middle among these carbon dots.

[0107] Figure 3 is the stress-strain curve of the hydrogel prepared in Comparative Example 1. Figure 3 It can be seen that the mechanical properties of polyvinyl alcohol hydrogel are 0.27MPa and 0.65MJ / m 3 This is because polyvinyl alcohol hydrogel has a high water content, which makes it flexible and absorbent, but also reduces the mechanical strength of the material. The presence of water weakens the mechanical strength of the PVA chain, causing the hydrogel to deform and break easily under stretching or pressure.

[0108] Figure 4 is the stress-strain curve of the hydrogel prepared in Comparative Example 2. Figure 4 It can be seen that the mechanical properties of citric acid-polyvinyl alcohol hydrogel are 1.06MPa and 1.5MJ / m 3 , which is a certain improvement over the mechanical properties of polyvinyl alcohol hydrogels. This is because citric acid has three carboxyl groups that can undergo cross-linking reactions with the hydroxyl groups in the PVA molecules. Citric acid forms cross-linking points with PVA molecules through these functional groups, which helps to form a tighter network structure, thereby increasing the strength of the hydrogel. Compared to pure PVA, citric acid can form cross-linking points between PVA chains, enhancing the stability and strength of the network structure. Although the cross-linking effect may not be as good as some specialized cross-linking agents, it is still better than pure PVA hydrogels without cross-linking.

[0109] Figure 5 is the stress-strain curve of the hydrogel prepared in Comparative Example 3. Figure 5 It can be seen that the mechanical properties of citric acid carbon dots-polyvinyl alcohol hydrogel are 11.55MPa and 71.6MJ / m 3 This is because citric acid carbon dots can form more cross-linking points in PVA hydrogel, making the network structure of the hydrogel more stable and compact. At the same time, the nano-size and excellent dispersibility of citric acid carbon dots improve the network density and cross-linking effect of PVA hydrogel. This improved network structure can effectively disperse and withstand external loads, thereby improving tensile strength and toughness.

[0110] Figure 6 is the stress-strain curve of the hydrogel prepared in Comparative Example 4. Figure 6 It can be seen that the mechanical properties of citric acid carbon dots-polyvinyl alcohol hydrogel after salting out treatment are improved to 18.04MPa and 72.38MJ / m 3 This is because sodium citrate enhances the network structure of the hydrogel by increasing the ionic strength and promoting the formation of cross-linking points. Secondly, the interaction between sodium ions and the functional groups of PVA and carbon dots further improves the cross-linking density and network stability. On the other hand, in the salt solution, osmotic pressure is formed inside and outside the PVA, making the PVA denser and enhancing its mechanical properties.

[0111] Figure 7 is the stress-strain curve of the hydrogel prepared in Comparative Example 5. Figure 7 It can be seen that the mechanical properties of the citric acid carbon dots-polyvinyl alcohol hydrogel after salting-out assisted progressive stretching are 52.7 MPa and 72.87 MJ / m 3 However, its elongation rate is significantly lower than that of the citric acid carbon dot-polyvinyl alcohol hydrogel after salting-out treatment. The reason is that during the gradual stretching process, the PVA long chains in the hydrogel will gradually orient under the action of external force to improve the mechanical properties. However, this gradual stretching will reduce the relative slip between the material chain segments, resulting in a decrease in strain.

[0112] Figure 8 The DSC graphs of the hydrogels prepared in Example 1 and Comparative Examples 1 to 5 are shown in FIG. Figure 8It can be seen that the DSC test shows that the freezing points of PVA are 2.18℃, PVA-CA: 1.98℃, PVA-CD: -2.8℃, PVA-CDY: -8.23℃, PVA-CDYS: -13.77℃, and PVA-CDYS: -12.81℃; their enthalpy changes are -136.4J / g, -112.5J / g, -102.4J / g, -47.28J / g, -23.84J / g, and -21.99J / g, respectively. Citric acid, as an organic acid, may slightly reduce the freezing point when dissolved in PVA. The introduction of citric acid carbon dots significantly reduces the freezing point. This is because the introduction of carbon dots increases the internal dispersion and heterogeneity of the hydrogel, which may promote the formation of more ice nuclei, resulting in a decrease in the freezing point. During the salting-out process, salt ions cause changes in the interactions between water molecules, causing the freezing point to drop. The stretched hydrogel may have undergone a structural rearrangement, making the structure of water molecules more compact, which in turn led to a significant decrease in the freezing point. This indicates that the combined treatment of stretching and salting out has a significant effect on the freezing point. After multiple salting out treatments, the freezing point increased slightly, but it was still lower than that of untreated PVA. This shows that multiple salting out further enhances the effect of salt on the behavior of water molecules, but the overall effect tends to be stable. For enthalpy change, the addition of citric acid reduces the enthalpy change because the interaction between citric acid and PVA changes the behavior of water molecules during solidification, thereby affecting the release of energy. Then further, the presence of carbon dots increases the complexity of the network, which reduces the energy release during solidification. Carbon dots introduce more heterogeneous nuclei, making the formation and melting of ice crystals more complicated. Subsequent salting out leads to more ions and modified structures in the hydrogel, all of which affect the release of energy during solidification. Salting out changes the thermodynamic properties of the solidification process and reduces the enthalpy change. The stretching process caused a more significant change in the internal structure of the hydrogel, resulting in a change in the arrangement of water molecules, making the energy changes during the solidification process more complex and less significant. After multiple salting out, the structural changes of the hydrogel tended to be stable, and the energy release during the solidification process decreased and tended to be balanced.

[0113] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A method for preparing a carbon dot-based superhydrogel, characterized in that the steps include: Using a carbon source as a raw material and water as a solvent, a carbon dot solution is prepared through firing and cooling; The carbon dot solution and polyvinyl alcohol are used as reactants, and subjected to high temperature reaction and freeze-thaw cycles to obtain a carbon dot-polyvinyl alcohol hydrogel; The carbon dot-polyvinyl alcohol hydrogel is subjected to salting-out assisted progressive stretching and then immersed in a sodium citrate solution to obtain the carbon dot-based super strong hydrogel; The carbon source is at least one of citric acid, tannic acid, malic acid and bark.

2. The preparation method according to claim 1, characterized in that: The usage ratio of the carbon source and water is 10 g:100 mL; the firing temperature is 160° C. and the firing time is 8 h.

3. The preparation method according to claim 1, characterized in that: The mass ratio of the carbon dot solution to polyvinyl alcohol is 17:3; the temperature of the high temperature reaction is 90° C. and the time is 3 hours.

4. The preparation method according to claim 1, characterized in that: The freeze-thaw cycle is freezing at -20°C for 8 hours, then thawing at 20°C for 3 hours, and the freeze-thaw cycle is repeated at least once.

5. The preparation method according to claim 1, characterized in that: The steps of salting-out assisted progressive stretching are: The carbon dot-polyvinyl alcohol hydrogel was immersed in a sodium citrate solution for 12 hours and then subjected to gradual stretching.

6. The preparation method according to claim 5, characterized in that: The concentration of the sodium citrate solution is 2 mol / L; the deformation amount of the progressive stretching is 300%.

7. The preparation method according to claim 1, characterized in that: The immersion time in the sodium citrate solution is 12 hours, and the concentration of the sodium citrate solution is 2 mol / L.

8. A carbon dot-based super strong hydrogel prepared by the preparation method according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Doped carbon quantum dot / PVA-based composite membrane, preparation method thereof and application in tetracycline detection

    CN113046071A

  • Method for preparing anisotropic programmable hydrogel based on boric acid ester bond and hydrogel

    CN114395142A

  • Preparation method of cellulose nanocrystal composite gel with orientation structure as well as product and application of cellulose nanocrystal composite gel

    CN115636953A

  • Boron-doped orange peel carbon dot modified hydrogel as well as preparation method and application thereof

    CN117463299A

  • Curcumin-carbon dot compound as well as preparation method and application thereof

    CN117925222A

Cited By

  • Polysaccharide-based high-permeability carbon dot hydrogel and preparation method thereof

    CN120059286A

  • A polysaccharide-based highly permeable carbon dot hydrogel and its preparation method

    CN120059286B

  • Preparation method of 3, 4-dihydroxybenzaldehyde / gelatin carbon nanomaterial-based adhesive hydrogel

    CN120098207A

  • Chlorophyll carbon dot-based hydrogel and preparation method thereof

    CN120118242A

  • A chlorophyll carbon dot-based hydrogel and its preparation method

    CN120118242B